Solid State Fermentation Of Rice Straw For Production Of Cellulases By Selected Fungi - Hayet Khan, Md. Munir (2007)

(untitled)
The production of cellulases from rice straw (RS) by four fungi: Trichoderma harzianum (SCahmT105), Trichoderma spp.(1) (STP101), Trichoderma spp.(3) (STP103) and Phanerochaete chrysosporium was investigated. The microbial treatment using solid state fermentation was conducted in 250 ml Erlenmeyer flasks considering rice straw as a major solid substrate. The highest cellulase activities such as 25.53 U/g of rice straw due to filter paper activity and 42.86 U/g of rice straw due to carboxymethyl cellulose activity were obtained at day 4 of cultivation using Phanerochaete chrysosporium for the purpose of selecting the best fungus among these four strains. Glucosamine for growth and reducing sugar as substrate utilization indicator were observed to evaluate the fermentation of rice straw in the experiment and pH values were recorded as well. Four process parameters of the solid state fermentation namely moisture content, mineral content, co-substratre and inoculum size with three levels of each parameter were used to optimize the production of cellulases by Plackett-Burman technique under factorial design. The results for first phase of optimization showed that the production of cellulases were higher i.e. 26.43 U/g of rice straw due to filter paper of activity and 46.25 U/g of rice straw due to carboxymethyl cellulose activity compared to the production obtained during the earlier study of selecting best strain among four fungi but the optimum regions of the surfaces was not found. Second phase of optimization was conducted to determine the actual optimum conditions within the ranges of variables tested. The experimental data were used to develop second order polynomial models considering linear, quadratic and interaction effects of the variables (factors). The optimum values obtained at second phase of optimization for moisture content, inoculum size, co-substrate and mineral content were 50% (v/w), 10% (v/w), 1% (w/w) and 5% (v/w) respectively. Using the final model equations the process factors/variables were tested by increasing or decreasing the values within the ranges of parameters tested and optimum production of cellulases were obtained to be 30.18 U/g of rice straw (FPU) and 53.93 U/g of rice straw (CMCase) for Phanerochaete chrysosporium with the optimum process conditions. A final experiment with these optimum process parameters of SSF was conducted to evaluate the production of cellulases as well as the validation of the models which indicated the production of 29.46 U/g of rice straw due to filter paper activity and 54.83 U/g of rice straw due to carboxymethyl cellulose activity in the laboratory which approved the optimum production obtained with 2.4% and 1.6% error, respectively.